Jenis-Jenis, Status Konservasi Dan Upaya Konservasi Tanaman Hias Langka Di Kota Banda Aceh Dan Kabupaten Aceh Besar - Kiki Monita; Ismul Huda; Hasanuddin Hasanuddin; Fatilah Erni (BIOEDUSCIENCE, 2021)
Background: Ornamental plants have their charm and high economic value, but their population in nature is decreasing. This study aims to determine the types of rare ornamental plants, conservation status and conservation efforts. Methods: The methods used in this research are qualitative methods and exploratory surveys. The population in this study were all sellers/entrepreneurs of Decorative Garden Plants in Banda Aceh City and Aceh Besar District. The research period was eleven months, from September 2019 to August 2020. The data was collected through an exploratory survey, using the IUCN Red List application and semi-structural interviews. Interviews were conducted using a questionnaire, and descriptive statistical analysis was carried out for conservation efforts. The questionnaire contains questions about conservation efforts with available answer options to gather information related to research. Results: The results showed that the types of rare ornamental plants consist of 32 species, the conservation status is dominated by minimal concern (56%) composed of 14 families. Conclusions: Rare ornamental plants are easily found in Kota Banda Aceh and Aceh Besar District. There is still a lack of conservation efforts such as protection, cultivation in preserving rare/endangered ornamental plants.